2022
DOI: 10.1021/acsami.2c06760
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance 1 cm2 Perovskite-Organic Tandem Solar Cells with a Solvent-Resistant and Thickness-Insensitive Interconnecting Layer

Abstract: Organic solar cells (OSCs) and perovskite solar cells (PVSCs) are promising candidates for next-generation thin film photovoltaic technologies. The integration of OSCs with PVSCs in tandem devices is now attracting significant attention due to their similar fabrication procedures and the potential to afford a higher device performance. Here, a thickness-insensitive and solvent-resistant interconnecting layer is developed to efficiently connect perovskite and organic subcells with low contact resistance. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Recently, Zhang et al incorporated C 60 ‐ionene to construct ICL with C 60 ‐ionene/Ag/MoO 3 structure. [ 354 ] Benefiting from the high conductivity, C60‐ionene‐based ICLs show a broad thickness processing window. The PCEs of corresponding devices maintained over a wide range of ICL thicknesses, from 20 to 50 nm, with the highest value being 19.2%.…”
Section: Interconnecting Layers In Monolithic Perovskite/organic Tand...mentioning
confidence: 99%
“…Recently, Zhang et al incorporated C 60 ‐ionene to construct ICL with C 60 ‐ionene/Ag/MoO 3 structure. [ 354 ] Benefiting from the high conductivity, C60‐ionene‐based ICLs show a broad thickness processing window. The PCEs of corresponding devices maintained over a wide range of ICL thicknesses, from 20 to 50 nm, with the highest value being 19.2%.…”
Section: Interconnecting Layers In Monolithic Perovskite/organic Tand...mentioning
confidence: 99%
“…The V OC values for PM6:Y6-based n-i-p SOSCs (0.78-0.83 V, Table 1) and p-i-n SOSCs (0.815-0.87 V, Table 2) undergo severe losses to the bandgap. [55][56][57] Consequently, novel organic materials with decreased V OC loss must be developed for enhancing the SOSCs performance and thereby, the POTSCs efficiency.…”
Section: Ocmentioning
confidence: 99%
“…Halide perovskite has become a very promising semiconductor material for the new generation of solar cells, light-emitting devices, and photodetectors. Its advantages are high-absorption coefficient, long carrier diffusion length, and convenient band gap adjustment in the visible light range, achieved by adjusting the proportion of halide precursors. Accurate control of the band gap provides an opportunity to integrate hybrid perovskite into light-emitting devices, lasers, and tandem solar cells. , In particular, the uninterrupted band gap from ∼1.77 to 2.38 eV makes the all-inorganic cesium lead halide an ideal choice for single junctions or tandem solar cells. In 2015, Hoke et al found that strong and reversible sub-band-gap photoluminescence characteristics were induced at ∼1.68 eV upon illumination with white light and reported the reversible photoinduced halide segregation (PIHS) phenomenon in hybrid halide perovskite films . However, PIHS causes homogenized halide ion segregation to form domains, and charge carriers are trapped in iodide rich regions, thus resulting in local changes in the material’s band gap. Thus, the practical applications of hybrid halide perovskite are limited. Therefore, it is crucial to determine the microscopic mechanism behind the PIHS to allow the development of methods to reduce the photoinduced effects in devices.…”
Section: Introductionmentioning
confidence: 99%